Linking Spatial and Temporal Dynamic of Bacterioplankton Communities With Ecological Strategies Across a Coastal Frontal Area - Lemonnier, Clarisse; Perennou, Morgan; Eveillard, Damien; Fernandez-Guerra, Antonio; Leynaert, Aude; Marié, Louis; Morrison, Hilary G.; Memery, Laurent; Paillard, Christine; Maignien, Lois (Frontiers in Marine Science, 2020)
Ocean frontal systems are widespread hydrological features defining the transition zone between distinct water masses. They are generally of high biological importance as they are often associated with locally enhanced primary production by phytoplankton. However, the composition of bacterial communities in the frontal zone remains poorly understood. In this study, we investigate how a coastal tidal front in Brittany (France) structures the free-living bacterioplankton communities in a spatio-temporal survey across four cruises, five stations and three depths. We used 16S rRNA gene surveys to compare bacterial community structures across 134 seawater samples and defined groups of co-varying taxa (modules) exhibiting coherent ecological patterns across space and time. We found that bacterial communities composition was strongly associated with the biogeochemical characteristics of the different water masses and that the front act as an ecological boundary for free-living bacteria. Seasonal variations in primary producers and their distribution in the water column appeared as the most salient parameters controlling heterotrophic bacteria which dominated the free-living community. Different dynamics of modules observed in this environment were strongly consistent with a partitioning of heterotrophic bacterioplankton in oligotroph and copiotroph ecological strategies. Oligotroph taxa, dominated by SAR11 Clade members, were relatively more abundant in low phytoplankton, high inorganic nutrients water masses, while copiotrophs and particularly opportunist taxa such as Tenacibaculum sp or Pseudoalteromonas sp reached their highest abundances during the more productive period. Overall, this study shows a remarkable coupling between bacterioplankton communities dynamics, trophic strategies, and seasonal cycles in a complex coastal environment.